Oil, development and nature: approaches to a scenario of expansion of extractive borders to the southeastern Amazon in Ecuador - Vallejo, Ivette (2014)
The article discusses the expansion of extractive frontiers in the southeastern region of Ecuador, with the bidding for oil blocksaround XI Round Oil. It presents the results of a research done 2013-2014, which aimed to analyze the bonds between extractiveand developmental policies and their effects on indigenous people’s territorial dynamics. The research included interviewing leaders ofindigenous organizations and government officials in the province of Pastaza, conducting thematic forums and monitoring of key events(forums), plus reviewing documentary sources. This article describes government policies that strengthen the developmental cosmography and coloniality of nature in the Amazon, and cause setbacks in the implementation of collective rights, while various positions,narratives and indigenous people agency activated conflicts around the control over territory and resources.